The hidden world of autism : writing and art by children with high-functioning autism - Chilvers, Rebecca (Jessica Kingsley, 2007)
A celebration of the talents and insights of children on the autism spectrum, "The Hidden World of Autism" presents a collection of writings and drawings contributed by 20 autistic children. The children's work covers topics that are of primary importance in understanding some of the common experiences that children with autism, and their families, go through. These include life before diagnosis, friendships, relationships, feelings, bullying and the future. A key characteristic of having autism is the inability to express emotions; but too often that prevents children with autism from being listened to. This book gives them both a voice and a forum for creative expression and provides direct insight into what having autism means for the children themselves and how they feel about their experiences. This unique collection provides invaluable insights into the autistic experience for professionals, families and friends of children with autism, as well as the children themselves.